Conventional Hemangiopericytoma: Modern Analysis of Outcome - Espat, N. J. (Institutional Knowledge at Singapore Management University, 2002)
BACKGROUND. Hemangiopericytoma (HPC) is a rare vascular tumor, and pathologic distinction from synovial sarcoma and solitary fibrous tumor is a significant problem due to shared histologic features. In the current report the authors defined the clinical behavior and prognosis for patients with HPC. METHODS. Between July 1982 and February 1998, 62 patients with a diagnosis of primary, recurrent, or metastatic HPC were identified from a prospectively maintained database. The pathology of all cases for which material was available (57 cases) was re-reviewed for histologic confirmation of the HPC diagnosis. Using strict pathologic criteria, including immunohistochemistry and electron microscopy, tumors from 25 of 57 patients qualified for the diagnosis of conventional hemangiopericytoma; those tumors formed the basis of the current report. Survival was determined by the Kaplan-Meier method. RESULTS. At the time of initial presentation, 19 patients had primary tumors, 3 had locally recurrent disease, and 3 had metastatic disease. The most frequent anatomic sites for HPC were the extremities, the pelvis, and the head and neck, accounting for 80% of the total cases. The median followup (n = 25) was 49 months (range, 1 to 160 months). The two and five year overall survival rates (n = 25) were 93% and 86% respectively. The disease-specific survival was 86% at last followup. Patients undergoing complete resection (n = 16) showed a 100% median survival at 60 months. CONCLUSIONS. At present, complete tumor resection for patients with conventional I IPC is recommended. However, considering the favorable outcome in this disease, the authors caution against performing operations that may potentially cause loss of function or are limb threatening.